A Case Report of An Iris Epithelial Cyst Masquerading As Iris Cysticercosis - Hoshing, Abhishek; Dhamankar, Rita; Tanwar, Shabnam; Bhat, Deepak (Nepalese Journal of Ophthalmology, 2020)
Introduction: Iris cysts can be primary or secondary. It is common to mistake a parasitic cyst for a benign pigment epithelial cyst. However, we report a case where a benign cyst was mistaken for a parasitic cyst. Case: A 50-year-old gentleman was seen in our OPD with gradual, progressive, painless diminution of vision in the right eye over past 5 Months. He was found to have a cystic lesion in the iris encroaching upon the pupil. Observations: Ultrasound biomicroscopy showed features characteristic of cysticercosis. In-toto excision of the cyst was done and was sent for histopathological examination. Histopathology failed to reveal features consistent with cysticercosis and instead showed characteristics of epithelial cyst of the iris. Conclusion: Histopathological examination should be done for all cystic lesions of the iris to confirm diagnosis.